Occupational Burnout Prevalence and Its Determinants Among Physical Education Teachers: A Systematic Review and Meta-Analysis - Alsalhe, Tariq A.; Chalghaf, Nasr; Guelmami, Noomen; Azaiez, Fairouz; Bragazzi, Nicola Luigi (Frontiers in Human Neuroscience, 2021)
Burnout can be defined as an occupational syndrome resulting from poorly managed chronic workplace stress. It is characterized by three dimensions: feelings of energy depletion or exhaustion; increased mental distance from one’s job, or feelings of negativism or cynicism related to one's job; and reduced professional efficacy. Teachers are among the human service professionals particularly vulnerable to occupational burnout. Teaching is a highly demanding and challenging task, in that requires constant confrontation with different stakeholders (students and their parents, administrators). Among teachers, physical education teachers have been particularly understudied even though a recently published systematic review has found that they are exposed to high levels of stress. To better explore burnout syndrome among physical education teachers, the present systematic review was undertaken. 56 studies were included in the present review. The reported rate of high emotional exhaustion ranged from 11.52% to 60.6%, according to the single study. Pooling together 12 studies and totaling 2,153 physical education teachers, the prevalence rate of high emotional exhaustion was computed to be 28.6 [95%CI 21.9-35.8]. The reported rate of high depersonalization ranged from 3.6% to 45.2%. Pooling together 11 studies and totaling 2,113 physical education teachers, the prevalence rate of high depersonalization was computed to be 14.5% [95%CI 8.0-22.4]. The reported rate of low personal accomplishment ranged from 13.63% to 55.6%, according to the single study. Pooling together 12 studies and totaling 2,153 physical education teachers, the prevalence rate of low personal accomplishment was computed to be 29.5% [95%CI 23.8-35.4]. The reported rate of overall burnout ranged from 10.0% to 51.6%,. Pooling together 7 studies and totaling 1,101 physical education teachers, the prevalence rate of overall burnout was computed to be 23.9% [95%CI 13.6-36.0]. No evidence of publication bias could be found. Burnout imposes a significant burden among physical education teachers. Based on the information contained in the present systematic review and meta-analysis, tailored interventions could be designed to mitigate such a burden. However, due to the limitations of the studies included in the present systematic review and meta-analysis, further research in the field is urgently warranted.